GENERAL CHARACTERISTICS OF PATIENTS WITH BRONCHIAL ASTHMA AND COMPLEX PROCEDURES OF DENTAL EXAMINATION - Salokhidin Z. Alavdinov (Central Asian Journal of Medicine, 2023)
Bronchial asthma is a serious problem in all countries of the world, including the Republic of Uzbekistan, which is also associated with a clear increase in the frequency of occurrence, the number of complications, exacerbation of the disease [1,6,7]. Studies in recent years have shown that about 2 million people in Uzbekistan suffer from bronchial asthma, of which about 1 million have severe forms of the disease. The prevalence rates for patients with bronchial asthma among the population are 30% mild , 50% moderate, and 20% severe bronchial asthma patients [5]. Bronchial asthma causes disability and major economic damage in the population. High rates of bronchial asthma have been reported in Uzbekistan. In 2019-2022, its prevalence in the Fergana region was studied, accounting for 7.2% [1]. Bronchial asthma has a single immune-inflammatory form that also affects the organs of the oral mucosa and the respiratory tract. In patients with bronchial asthma, the oral cavity has a significant effect on the decrease in the protective properties of the mucous membrane, which creates unfavorable conditions for the hard tissues of the tooth and periodont tissue, increases the effect of microflora and other pathogenic factors. There is information about the presence of disorders in the immune system in patients with bronchial asthma who are prone to the occurrence of inflammatory periodontal diseases [2,4,9]. Both an attack of bronchial obstruction and a relatively calm period of the disease require the appointment of medications, in particular glucocorticosteroids. At the same time, along with a positive effect, these drugs lead to a decrease in the natural protective barrier of the oral mucosa and dysfunction of immune defense systems. This can significantly complicate adequate therapy of the disease, contributing to the development or progression of local and general inflammatory diseases [11,12]. With the beginning of the use of glucocorticosteroids, the results of preventive and maintenance therapy of bronchial asthma have improved significantly, but currently the effect of these drugs on the condition of the oral mucosa is little studied. Studies have not been carried out in patients with bronchial asthma, taking into account the condition of the oral cavity, the clinical and pathogenetic variant, duration and methods of this disease [4].